Impact of Bone Scan on Management of Breast Cancer Patients - Masood Ahmed Qureshi, Mushtaque Ahmed Abbasi, Muhammad Sharif Awan, Muhammad Nawaz Abro, Imtlaz All Langah, Aijaz Hussain Awan, Naeem Karim Bhatti , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the impact ofbone scan on breast cancer management its benefits and harms. Methods: This multicenter prospective observational study was conducted at surgical Unit III of Peoples University of Medical and Health Sciences for women, Jirtna.h Medical Center and NORIN Cancer Hospital, Nawabshah, from Jan 2014 to Dec 2016. In this study150 females breast cancer patients diagnosed on histopathology without any prior systemic therapy were included. Triple assessment, including detailed history, clinical examination, radiologic assessment and histopathology for confirmation of type of carcinoma was performed in all patients. Bone scan was advised to observe the bone metastasis. Inclusion criteria were all recently diagnosed patients with breast carcinoma. Exclusion criteria were recurrent disease and the patients received oncology treatment such as radiotherapy, chemotherapy or hormone therapy. Data analysis done on SPSS 21 version Results: There was wide variation of age ranging from 30 to 65 years. The mean age was 41± 3.2 years. Risk factors of breast cancers were age over 40 years in 109(72.66%) cases followed positive family history of breast cancer in 51 (34%) cases. The size of malignant breast lumps ranged from 2.2 cm to 13 cm with a mean size of 6.6 ± 2.7, On examination, findings were irregular margins in 98 (65.33%) cases, hard consistency in 120 (80%), firm to hard consistency in 30 (20%), tumor size > 2 cm 136 (90.66%) patients. 7 (4.66%) patients of stage 111 had positive skeletal metastasis while 11 (7.33%) patients of stage IV had positive skeletal metastasis. Conclusion: We conclude that bone scan should be done in stage HI breast cancers. Presence of such lesion in association with normal radiograph appears highly suspicious of occult metastases.